Biodiversity, road transport and urban planning: A Swedish local authority facing the challenge of establishing a logistics hub adjacent to a Natura 2000 site. (June 2021) - Sandström, Ulf G.; Elander, Ingemar
Highlights: A local authority trying to harmonize biodiversity and city growth in a siting case. Analytical approach combining multilevel governance, negotiating planning and narrative method. Inside analysis of a planning process in face of conflicting interests. Urban planning between regulation and negotiation. Biodiversity, urban sustainability and/or resilience? Abstract: The aim of the article is to analyse and reflect upon the process and outcome of a potential clash between urban biodiversity and road transport interests in the Swedish city of Örebro, as a case of planning in the face of conflict. Combining an application of multilevel governance theory with negotiation planning and narrative method, it examines the siting of a huge warehouse and "logistics centre" at the edge of a Natura 2000 site on the outskirts of the city. Despite the city's ambitious environmental goals and sustainability profile, the local authority decided to offer the company a site adjacent to a wetland area intended for preserving and developing biodiversity. After an intervention by the central state County Administrative Board [ länsstyrelsen ], the local authority had to implement certain security measures, and also reserve an additional, large natural land area to compensate for the threats to the Natura 2000 site. Before the final decision was made, a series of negotiations occurred between the involved actors, mainly the local authority, the multinational Sonepar Group/Elektroskandia and the County Administrative Board, and the case is a fruitful target for a multifaceted analysis illuminating the tension between the goals of preserving urban biodiversity and promoting road transport and urban growth. It also offers an inside view of the negotiation and planning process. The key issue is how the siting of a potentially hazardous, transport intensive national warehouse in a city renowned for its high environmental-protection profile was possible. Considering Sweden's high-profile regarding sustainability, the selected case also offers food for reflection on the potentials and barriers of implementing ecological modernization more generally. The lessons learned from an examination of the local authority's attempt to harmonize such diverse policy priorities as urban biodiversity and intensive road transport for economic growth, on a site adjacent to a Natura 2000 wetlands area, may help enable urban planners and scholars to find creative policy solutions, avoid causing damage to biodiversity, and increase ecosystem values in terms of residents' and other visitors' experience and understanding of nature. However, at the end of the article we address the question of whether our empirical conclusion is not "too good to be true", and raise concerns regarding the intricate relationship between sustainability and resilience; the systemic power exerted by the global Sonepar Group/Elektroskandia; and the potentials and limits of public negotiation planning.